2002
DOI: 10.1016/s0893-133x(02)00318-4
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 1A Receptor Activation and Hypothermia in Humans Lack of Evidence for a Presynaptic Mediation

Abstract: The hypothermia produced by 5-HT 1A 1A receptors are located both on the cell body of 5-HT neurons and on postsynaptic neurons throughout the central nervous system. On 5-HT neurons, 5-HT 1A receptors mediate a negative feedback influence on firing activity. When overactivated by an excess amount of 5-HT, or by an exogenous agonist, they slow down the pacemaker activity leading to a decreased firing rate of 5-HT neurons (Aghajanian and Lakoski 1984;Blier and de Montigny 1987). As 5-HT release is proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 38 publications
(56 reference statements)
3
29
0
Order By: Relevance
“…In subsequent work, we found that systemic 8-OH-DPAT rapidly reversed the sympatholytic response to hypotensive hemorrhage when administered after establishment of hypotensive hemorrhage (Scrogin, 2003). In addition, 5-HT1A receptor agonists reduce core body temperature and stimulate the release of endogenous adrenocorticotropin hormone, both of which have been found to have beneficial effects in suppressing reperfusion injury after resuscitation from hypovolemic shock (Guarini et al, 1990;Vicentic et al, 1998;Blier et al, 2002;Takasu et al, 2002). Together, these stud- jpet.aspetjournals.org ies suggest that lipophilic 5-HT1A receptor agonists have potential as adjuncts to volume resuscitation in the treatment of hypovolemic shock.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In subsequent work, we found that systemic 8-OH-DPAT rapidly reversed the sympatholytic response to hypotensive hemorrhage when administered after establishment of hypotensive hemorrhage (Scrogin, 2003). In addition, 5-HT1A receptor agonists reduce core body temperature and stimulate the release of endogenous adrenocorticotropin hormone, both of which have been found to have beneficial effects in suppressing reperfusion injury after resuscitation from hypovolemic shock (Guarini et al, 1990;Vicentic et al, 1998;Blier et al, 2002;Takasu et al, 2002). Together, these stud- jpet.aspetjournals.org ies suggest that lipophilic 5-HT1A receptor agonists have potential as adjuncts to volume resuscitation in the treatment of hypovolemic shock.…”
Section: Discussionmentioning
confidence: 93%
“…5-HT1A receptor agonists have additional effects that may provide an advantage over hypertonic saline use during volume resuscitation. For instance, systemically administered 5-HT1A receptor agonists can readily cross the blood-brain barrier and act on thermoregulatory centers to reduce body temperature (Blier et al, 2002). Recent work indicates that mild hypothermia reduces reperfusion injury after resuscitation from hypovolemic shock (Takasu et al, 2002;Takasu et al, 2003).…”
mentioning
confidence: 99%
“…7D) or intravenous injection of leptin (92,107), as well as shivering evoked by cooling or PGE 2 injection into the POA (18,106). These sympathoinhibitory effects of 5-HT 1A receptor agonists through their action in the rMR might be a major pharmacological cause of severe hypothermia observed following systemic administration of such drugs in rats (52), mice (43), and humans (11). Activation of 5-HT 1A receptors is considered to inhibit neuronal functions through their negative coupling to adenylate cyclase via G i proteins (6), and these receptors are located in spinal projecting neurons in the medullary raphe region (50).…”
Section: Bulbospinal Premotor Signaling From Rmr Neuronsmentioning
confidence: 99%
“…In rats (e.g., Millan et al 1993b;Bill et al 1991;Goodwin et al 1987) and humans (Blier et al 2002), 5-HT 1A receptor-induced hypothermia is thought to be mediated by postsynaptic 5-HT 1A receptors, while in mice, the somatodendritic 5-HT 1A receptors seem to be involved (Goodwin et al 1985;Martin et al 1992), although some controversies regarding the pre-and postsynaptic modulation of 5-HT 1A receptor-mediated hypothermia in rat exist (Higgins et al 1988;Hillegaart 1991). However, combined with our observation that 8-OHDPAT-induced activity and 5-HT syndrome, which are postsynaptically mediated (Yamada et al 1988), were reduced in SERT −/− rats relative to SERT +/+ rats in the locomotor tests, the 8-OHDPATinduced hypothermia findings imply that predominantly postsynaptic 5-HT 1A receptors are involved.…”
Section: Enhanced Rewarding Properties Of Cocaine In Sertmentioning
confidence: 99%